(untitled) (Al-Mansour Journal, 2022)
The pursuit of the Algerian economy to integrate into the new global trading system Through to join upcoming to World Trade Organization. Constitutes a challenge for small enterprises and the Algerian medium, both at the level of diversification of markets or product diversification, Considering that join forces to open markets to facilitate the flow of goods and services across international borders and to the lack of international intervention and the freedom of trade, leading to heightened competition through increased presence of foreign institutions to maintain its market share. Therefore look to the future prospects of this join requires put a planned an ambitious and effective to restructure SMEs and rehabilitated so that they can gain a competitive capability enabling it to withstand the shock of integration, and strengthen its presence on the level of foreign markets.